Stitching tivaevae: a Cook Islands research method. (June 2019) - Futter-Puati, Debi; Maua-Hodges, Teremoana
The use of a context-specific research model is critical when undertaking research that involved Pacific people. This article discusses the use of a Kuki Airani | Cook Islands research framework known as the Tivaevae Model in a PhD study. This model first introduced by Maua-Hodges borrows from the traditions of creating a traditional tivaevae | handmade quilt. The tivaevae represents Kuki Airani epistemological and ontological worldviews. Utilising the processes used to create a tivaevae as a metaphor and guiding process, the research was stitched together to develop a metaphorical tivaevae symbolising aronga mapu | youth views of sexuality. This article discusses the research process and how the tivaevae model was used through data collection, analysis, findings design and the educational "project." In doing so, this article examines the research process that is contextually and culturally appropriate to better understand the nuances of what indigenous research methods can potentially offer, both conceptually and methodologically to critical researchers.